2022
DOI: 10.3389/fbioe.2022.797437
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanoparticle-Mediated Orientation of Collagen Hydrogels for Engineering of Tendon-Mimetic Constructs

Abstract: Despite the high incidence of tendon injuries worldwide, an optimal treatment strategy has yet to be defined. A key challenge for tendon repair is the alignment of the repaired matrix into orientations which provide maximal mechanical strength. Using oriented implants for tissue growth combined with either exogenous or endogenous stem cells may provide a solution. Previous research has shown how oriented fiber-like structures within 3D scaffolds can provide a framework for organized extracellular matrix deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…A few studies had proposed the roles for magnetic-responsive biomaterial in promoting tissue regeneration. Aligned collagen fibers mediated by IOPs mimicked the structure of native tendon and could be used in tendon repair . In addition, a hydroxyapatite scaffold increased vascularization and bone regeneration via releasing vascular endothelial growth factor (VEGF) in a magnetic-controlled manner .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies had proposed the roles for magnetic-responsive biomaterial in promoting tissue regeneration. Aligned collagen fibers mediated by IOPs mimicked the structure of native tendon and could be used in tendon repair . In addition, a hydroxyapatite scaffold increased vascularization and bone regeneration via releasing vascular endothelial growth factor (VEGF) in a magnetic-controlled manner .…”
Section: Discussionmentioning
confidence: 99%
“…Aligned collagen fibers mediated by IOPs mimicked the structure of native tendon and could be used in tendon repair. 24 In addition, a hydroxyapatite scaffold increased vascularization and bone regeneration via releasing vascular endothelial growth factor (VEGF) in a magnetic-controlled manner. 25 In this study, the magnetic-responsive coating coordinately interacting with magnetic field, as a combination of biochemical and physical properties, was expected to modulate macrophage polarization and enhance osteointegration.…”
Section: Discussionmentioning
confidence: 99%
“… , However, magnets with such a high magnetic field induction are quite difficult to find and may often be prohibited for use in many laboratories. Therefore, magnetic nanoparticles are often used to produce anisotropic hydrogels, which move toward the magnet and through their motion align the fibrils, which then bind. This kind of experiment requires a magnetic field with much lower induction.…”
Section: Methods To Controlling the Aligned Structure In Hydrogelsmentioning
confidence: 99%
“…These results highlight the feasibility of using magnetically anisotropic hydrogels for developing tendon-mimicking connective tissues. Furthermore, Wright et al 113 prepared collagen I hydrogels with anisotropic structures by adding anti-collagen I-labeled MNPs to a fluorescent collagen solution and immersing them in a 50–52 mT magnetostatic field for 30 min. It was observed that the F-actin filaments of hASCs seeded within the magnetically anisotropic hydrogel were unidirectional, parallel to the orientation of MNPs and fibrous collagen (Fig.…”
Section: Tissue Engineering Applications Of Magnetically Anisotropic ...mentioning
confidence: 99%